MOSkin dosimetry for an ultra-high dose-rate, very high-energy electron irradiation environment at PEER - Cayley, James; Tan, Yaw-Ren E.; Petasecca, Marco; Cutajar, Dean; Breslin, Thomas; Rosenfeld, Anatoly; Lerch, Michael (Frontiers in Physics, 2024)
FLASH radiotherapy, which refers to the delivery of radiation at ultra-high dose-rates has been demonstrated with various forms of radiation and is the subject of intense research and development recently, including the use of very high-energy electrons to treat deep-seated tumours. Delivering FLASH radiotherapy in a clinical setting is expected to place high demands on real-time quality assurance and dosimetry systems. Further, very high-energy electron research currently requires the transformation of existing non-medical accelerators into radiotherapy research environments. Accurate dosimetry is crucial for any such transformation. In this article we assess the response of the Centre for Medical Radiation Physics developed MOSkin, designed for on-patient, real-time skin dose measurements during radiotherapy and whether it exhibits dose-rate independence when exposed to 100 MeV electron beams at the Pulsed Energetic Electrons for Research (PEER) end-station. PEER utilises the electron beam from a 100 MeV linear accelerator when it is not used as the injector for the ANSTO Australian Synchrotron. With estimated pulse-dose-rates of (7.84 ± 0.21) × 10 5 Gy/s to (1.28 ± 0.03) × 10 7 Gy/s, and an estimated peak bunch-dose-rate of (2.55 ± 0.06) × 10 8 Gy/s, MOSkin measurements were verified against a scintillating screen to confirm the MOSkin responds proportionally to the charge delivered and, therefore, exhibits dose-rate independence in this irradiation environment.